1998
DOI: 10.1073/pnas.95.1.29
|View full text |Cite
|
Sign up to set email alerts
|

The microwave background anisotropies: Observations

Abstract: Most cosmologists now believe that we live in an evolving universe that has been expanding and cooling since its origin about 15 billion years ago. Strong evidence for this standard cosmological model comes from studies of the cosmic microwave background radiation (CMBR), the remnant heat from the initial fireball. The CMBR spectrum is blackbody, as predicted from the hot Big Bang model before the discovery of the remnant radiation in 1964. In 1992 the cosmic background explorer (COBE) satellite finally detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These micropollutants have also accumulated in the soil through adsorption and in animals through bioaccumulation 14, 15. In a global study of rivers in 104 countries, active pharmaceutically ingredients were found in a quarter of the studied 1052 locations 16.…”
Section: Introductionmentioning
confidence: 99%
“…These micropollutants have also accumulated in the soil through adsorption and in animals through bioaccumulation 14, 15. In a global study of rivers in 104 countries, active pharmaceutically ingredients were found in a quarter of the studied 1052 locations 16.…”
Section: Introductionmentioning
confidence: 99%
“…The DMR did not have much margin to spare: The year 1 data had an S/N of about 1 per pixel (roughly a 100-square-degree patch), which increased to about 2 in the final 4-year data set. The detection of anisotropy on the 10°scale was highly significant, but the features in the map were much less so(107).www.annualreviews.org • Precision Cosmology…”
mentioning
confidence: 99%
“…The orthodox picture of an isotropic and homogeneous universe (Friedmann universe) as strongly supported by the cosmic microwave background radiation [1] and the cosmological principle is at stake today as three-dimensional redshift surveys prober deeper into the universe uncovering more inhomogeneous structures (fractal) on large length scales [2]. The existence of structures like galaxies in clusters and voids is believed to point towards inhomogeneities and therefore, raises the question as to whether or not visible matter distribution really becomes homogeneous on certain length scale or if the fractal model is as a result of misinterpretations of the limited available observational data of the universe.…”
Section: Introductionmentioning
confidence: 99%